RESPON PETANI KARET TERHADAP PEMBENTUKAN PROGRAM GABUNGAN KELOMPOK TANI DIDESA SUNGAI KUNING BINIO KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Handayani, Siska; Yoserizal, H. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Abstract               This research was carried out In the village Sungai Kuning Binio Indragiri Hulu Regency, Kabupaten Indragiri Hulu. The purpose of this research is to know the management (menajemen) a combined group of farmers In the village Sungai Kuning Binio Indragiri Hulu Regency, Kabupaten Indragiri Hulu. The topic of this research focus is about the response of the community towards a combined group of farmers In the village Sungai Kuning Binio Indragiri Hulu Regency, Kabupaten Indragiri Hulu. Sample determination techniques in Simple Random Sampling, and set the number of samples as many as 53 people. The author uses descriptive quantitative methods and instruments of data are observation, question form and documentation. Study conducted found 92.5% of respondents say that gapoktan supports the farmer community with seeking farmer input. 69.8% of respondents say that gapoktan supports the farmer gapoktan who is a member of the community by providing save capital borrowed. 81.1% of respondents say that gapoktan supports the farmer community by monitoring regarding the treatment of farmer. 100% of respondents said that they learned well the purpose, the terms joined by gapoktan, and knowledge about other gapoktan. 100% of respondents say they agree with the presence of gapoktan. 72.6% of respondents said that they followed the activities organised by the gapoktan Keywords: Farmer, Community Response